Association of Decreased Serum BDNF With Restless Legs Syndrome in Parkinson's Disease Patients - Huang, Yi-xian; Zhang, Qi-lin; Huang, Cai-li; Wu, Wen-qi; Sun, Jia-wei (Frontiers in Neurology, 2021)
Objective: To investigate whether serum Brain-derived neurotrophic factor (BDNF) levels are associated with the severity of restless legs syndrome (RLS) in Parkinson’s disease (PD). Methods: A total of 249 PD patients with (n = 53) and without RLS (n = 196) and 326 age-matched controls were included in this study. All participants’ serum BDNF levels were measured. International Restless Legs Syndrome Study Group Rating Scale (IRLSSG-RS) was administered for the severity of RLS. The severity of PD patients were assessed by the Unified PD Rating Scale (UPDRS) and the Hoehn and Yahr (H-Y) stage. Results: The prevalence of RLS were significantly higher in PD patients (21.3%) than in the controls group (7.4%) (p < 0.05). The IRLSSG-RS score in PD patients with RLS (16.25±5.24) was significantly increased than in controls with RLS (12.08±3.99) (p < 0.01). The serum BDNF levels were significantly decreased in PD patients with RLS than PD patients without RLS, controls without RLS and controls with RLS (p < 0.001). BDNF levels were negatively associated with IRLSSG-RS in both PD patients with RLS and controls with RLS group (both p < 0.01). Multiple regression analysis confirmed that in either PD with RLS or controls with RLS group, BDNF was an independent contributor to IRLSSG-RS (both p < 0.01). Conclusions: Decreased serum BDNF levels may be involved in the pathophysiology of RLS in PD, suggesting that it may serve as a potential blood biomarker of diagnostic value for RLS in PD.